Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Solve the linear equation 2(3x + 2) = 2x – 1 + x. State the property that justifies your first step and why you
chose it.


Sagot :

Answer:

x = -5/3

Step-by-step explanation:

2(3x + 2) = 2x - 1 + x

2 × 3x + 2 × 2 = 2x + x - 1

6x + 4 = 3x - 1

3x = -5

x = -5/3

Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.